2013
DOI: 10.1590/s1413-81232013000800015
|View full text |Cite
|
Sign up to set email alerts
|

Histórias de aborto provocado entre adolescentes em Teresina, Piauí, Brasil

Abstract: This paper analyses the methods, techniques and support networks taken by adolescents to perform illegal abortions. It is a descriptive and cross-sectional study involving interviews with 30 adolescents who had been hospitalized for uterine curettage in two public hospitals in Teresina between June and November 2011. Informed consent was given orally, and the interviews were recorded after the confirmation of the induced abortion. The adolescents were between 14 and 17 years old, single, and predominantly live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
0
7
0
14
Order By: Relevance
“…Misoprostol and other drugs are the most referred methods, whereas the use of tea is associated with the attempt of normalizing menstrual cycle. In these cases, nonsignificant results may be explained by the fact that not all women recognize the use of teas and home preparations as abortifacient methods because they are integrated in their routines or are treated as contraceptive methods 8,22,31,32 . This study had some limitations; however, those limitations could not prevent the study from being conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Misoprostol and other drugs are the most referred methods, whereas the use of tea is associated with the attempt of normalizing menstrual cycle. In these cases, nonsignificant results may be explained by the fact that not all women recognize the use of teas and home preparations as abortifacient methods because they are integrated in their routines or are treated as contraceptive methods 8,22,31,32 . This study had some limitations; however, those limitations could not prevent the study from being conducted.…”
Section: Discussionmentioning
confidence: 99%
“…This may occur because the majority of women who have better purchasing power, and who can afford health insurances, or pay for the procedure, opt for private health-care services. However, it is worth mentioning that most research on abortion used as sample only portion of women hospitalized because of abortion complications, and women who seek for the Unified Health System, demonstrating the induction of common selection bias in these studies 22,32 . Second, the type of abortion (spontaneous or induced) was not identified because of the possibility of reducing selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…In North America, 50% of all pregnancies are unexpected or unplanned, and, in Brazil, a previous study reported that 48% of pregnant women between the ages of 18 and 39 use abortifacient drugs (3,27) . Misoprostol is the main method (94%) used to induce illegal abortions among adolescents in the State of Piauí (northeastern Brazil), and this drug was associated with herbal tea in one case (11) . In the current study, the majority of mothers (90.2%) of patients with Möbius sequence reported an unplanned pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of abortive medications, such as misoprostol and certain herbal teas, are common in these countries (7,8) and are associated with congenital anomalies (7,(9)(10)(11) . Möbius sequence is a rare congenital disorder with an estimated prevalence in the general population of 1:500 to 1:5,000 newborns (7,12) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation